1998
DOI: 10.1159/000030023
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Variants of Human Alpha-Fetoprotein

Abstract: The immunological heterogeneity of human α-fetoprotein (AFP) was demonstrated using immunoaffinity electrochromatography on monoclonal antibodies (MoAbs) to 3 non-cross-reacting epitopes of this protein. At least 4 subfractions expressing different epitopes were found in the native AFP. These subfractions demonstrated molecular weights similar to the major component of the original AFP. The difference between epitope F5-positive and F5-negative subfractions disappeared when epitope-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…All these findings strongly suggest the cryptic nature of cluster D epitope. The full proof of this suggestion is given in the accompanying paper [12].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…All these findings strongly suggest the cryptic nature of cluster D epitope. The full proof of this suggestion is given in the accompanying paper [12].…”
Section: Discussionmentioning
confidence: 85%
“…The former type of competition was very clearly expressed between clusters A and D. One possible explanation of unidirectional cross-reactivity could be MoAbs' identical specificity but significant difference in the affintiy to the same epitope. In this case it might be expected that the high-affinity The partial competition phenomenon which was observed with certain MoAb pairs could be explained by the existence of the epitope variants in AFP [12]. In this case, the MoAb would inhibit only a fraction of AFP possessing the corresponding epitope.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier we proposed an approach for the separation of proteins into fractions based on the expression of individ- ual epitopes in the native molecule, which also demonstrated that AFP preparations contained several epitope variants [10,11]. Since the AFP structure is determined by a single gene representing a single polypeptide chain with varying oligosaccharide moieties [3], these different epitope variants would appear to be conformational ones of the same polypeptide chain.…”
Section: Introductionmentioning
confidence: 99%
“…Since the AFP structure is determined by a single gene representing a single polypeptide chain with varying oligosaccharide moieties [3], these different epitope variants would appear to be conformational ones of the same polypeptide chain. Indeed, one of the AFP epitopes was shown to exist in both an antibody accessible form (defined as the epitope + or ep + variant), and in a cryptic form (defined as the epitope -or ep -variant) [11].…”
Section: Introductionmentioning
confidence: 99%
“…These results were almost identical to that found by Dr. Nustad et al [17] and Kamakura [18] found that one of the epitopes did apparently contain carbohydrate in their studies. Dr. Karamova et al [19] …”
mentioning
confidence: 99%